ANALISIS NILAI-NILAI MULTIKULTURAL PADA SISWA KELAS VII G DI SMP NEGERI 2 PONTIANAK - Pera, Feti; Bahari, Yohanes; Fatmawati, Fatmawati (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to find out about, " multicultural values in VII G grade student in SMP Negeri 2 Pontianak. The problem is as follow : how is cultural awareness and sensitivity of VII G student in SMP Negeri 2 Pontianak ? how is the cultural tolerance and how to reasponsive grade .The porpose of this study was to determine cultural awareness and sensitivity,cultural tolerance and cultural responsive in clas VII G student in Negeri 2 Pontianak.this research is a qualitative research with a descriptive approach.informants obtained through direct observation,interviews, and documentation..data validations used is triangulation,data soursece and time. The result of this study indicate that 1) cultural awareness and sensitivity in students can be seen from students who know each other friends with Â in their classroom also show sensitivity by helping each person so as to provide understanding to student about multicultural values. 2)cultural tolerance is seen from student who respect and respect each other especially in religious activities and can be seen from the way. 3)students cultural responsiveness can be seen from students accepting their peers in one class Â Keywords: cultural, student, awareness,sensitivity,tolerance,responsive